ANALISIS KESULITAN MEMBACA AWAL PADA SISWA KELAS 1 SD - Yulita Ania Rahman; Rina Susi Cahyawati (Berajah Journal, 2026)
This study aims to analyze early reading difficulties among first-grade elementary school students and the factors influencing them, including students’ reading interest. The research employs a qualitative approach using a phenomenological method to explore students’ learning experiences in depth. The subjects of this study are first-grade students who experience difficulties in beginning reading. Data were collected through initial reading tests and in-depth interviews. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that early reading difficulties include the inability to consistently recognize letters, difficulty in connecting letters with their sounds, hesitant or halting reading, and low comprehension of simple texts. These difficulties occur in stages and show that students have not yet reached reading fluency and comprehension. Furthermore, the study reveals that reading difficulties are influenced by several factors, including physiological, intellectual, environmental, and psychological aspects. One significant factor is students’ low reading interest, which affects their engagement and practice in literacy activities. To address these challenges, appropriate and varied instructional strategies are needed, such as the phonics method, the use of engaging learning media, and repeated reading activities. Support from teachers and parents is also essential in improving students’ reading interest and ability. Therefore, systematic and continuous efforts are expected to enhance students’ early reading skills.